Barry Le Va : the aesthetic aftermath - Maizels, Michael, 1983- (University of Minnesota Press, 2015)
Of the conceptual artists who began their careers in the 1960s and 1970s-Bruce Nauman, Chris Burden, Vito Acconci, and Mel Bochner among them-Barry Le Va may be the most elusive. As this first study of his work reveals, his rigorously planned art was instigated to mask its creator's intentions and methods, presenting itself as an "aftermath" of modernism's claim to permanency and civil society's preferred mode of monumentalism. For Michael Maizels, Le Va's work constitutes a particularly productive subject of inquiry because it clearly articulates the interconnection between the avant-garde's distrust of autonomous art objects, two decades of social unrest, the emergence of information theory, and lingering notions of scientific objectivity. Barry Le Va: The Aesthetic Aftermath explores how Le Va used such materials as shattered glass, spent bullets, sound recordings, scattered flour, and meat cleavers embedded in a floor to challenge the interlocking assumptions behind blind faith in lasting beauty, just government, and perfectible knowledge. Taking inspiration from popular crime novels as well as contemporary art theory, Le Va charged his viewers to attempt, like detectives at a crime scene, to decipher an order underlying the apparent chaos. Le Va's installations were designed to erode not simply the presumed autonomy of the art object but also the economic and political authority of the art establishment. In his concluding chapter, Maizels looks at the more fixed work of the past two decades in which Le Va turned to architectural themes and cast concrete to probe the limits of dynamism and the idea of permanence.